Double Jeopardy: COVID-19, coup d'etat and poverty in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
Myanmar experienced four distinct COVID shocks to its economy over 2020 to early 2022 as well as a military takeover in February 2021 that created severe political, civil and economic turmoil. COVID and the coup d’état reversed a decade of growth and poverty reduction, but the full extent of the crisis on household poverty has remained uncertain because of the challenges of conducting large-scale in-person welfare surveys during the pandemic and recent political instability. Here we combine ex ante simulation models with diverse phone survey evidence from mid-2020 to early 2022 to estimate the poverty impacts of these shocks and some of the mechanisms behind them. Both simulations and surveys are consistent in painting a grim picture of rising poverty, capital-depleting coping mechanisms, and the complete collapse of government-provided social protection.